Uns composts valencians en llur context romànic - Colón Domènech, Germà (Caplletra. Revista Internacional de Filologia, 2015)
As it seems, Catalan does not have a system which, as in the case of related languages (like for instance Occitan boui-abaisso; French tournevire; Spanish muerdehuye), allows to form new nouns by means of assembling two verbal forms of Imperative. Prof. Colón studies some of the few instances where this special construction has been documented in Catalan and he reaches the conclusion that all of them seem to be loans from other languages.